Fördern Geldpolitik und Niedrigzinsen einen nachhaltigen Rückgang der Staatsschulden? - Hans-Jörg Naumer (Wirtschaftsdienst, 2015)
Die aktuell verbreitet niedrigen Zinsen mindern die Belastung durch die öffentliche Kreditaufnahme. Doch wird sich die Schuldenstandsquote EU-weit in Richtung auf das Maastricht-Kriterium von 60% des Bruttoinlandsprodukts zubewegen? Der Autor zeigt anhand modellhafter Betrachtungen, dass der Schuldenabbau über die Schuldenkrise in Griechenland hinaus für die gesamte Eurozone eine Aufgabe bleibt. – – Huge parts of the yield curve in several countries of the European Monetary Union entered negative territory after the European Central Bank started its Public Sector Purchase Programme (PSPP) in March 2015. The implicit interest rate for public deficits therefore has reached new lows after years of yield reductions. This paper will show that even such a favourable yield environment will not lead to a sustainable reduction of debt-to-GDP ratios and that it takes more than just low or negative yields to bring these ratios back in line with the Maastricht level of 60 per cent. This will be even more apparent when long-term yields head back to normal, driving the real rate of interest above the real rate of growth.
Keywords: E50; G10; H62; 330; Öffentliche Schulden; Niedrigzinspolitik; Schuldenmanagement; Schuldenkrise; Szenariotechnik; Eurozone